Feeding the feelings: gender differences in emotional eating during COVID-19: a systematic review and meta-analysis - Zaiser, Christopher; Pahlenkemper, Marie; Brandt, Gerrit; Ballero Reque, Cristina; Sabel, Luisa; Laskowski, Nora M.; Paslakis, Georgios (Frontiers in Nutrition, 2025)
ContextThe COVID-19 pandemic intensified mental health issues and increased emotional eating (EE), a coping mechanism, where food is consumed in response to emotions rather than hunger. During the pandemic, gender-specific EE patterns were observed, with women reporting elevated EE levels in response to stress, anxiety, and depression due to various social and psychological factors.ObjectivesThis study primarily focused on examining gender differences in EE during the COVID-19 pandemic. As a secondary outcome, it aimed to explore predictors of EE.Data sources and extractionThis systematic review was pre-registered (PROSPERO CRD42023421727) and adhered to PRESS and PRISMA guidelines. Studies published between March 2020 and August 2024 were identified across Scopus, Web of Science, PubMed, and PsycINFO. The quality assessment was performed using the “Critical Appraisal Checklist for Analytical Cross-Sectional Studies.” The meta-analysis was conducted following MOOSE guidelines.Data analysisOf 14,347 studies identified, 30 met inclusion criteria (only if population ≥18 years, without clinical diagnoses, gender-specific analysis regarding EE, observational studies with original data collection during COVID-19 pandemic), with 16 incorporated into the meta-analysis. Gender significantly moderated pandemic-related stress. Higher EE scores in women were linked to isolation and caregiving responsibilities, while men’s EE often appeared as reward-seeking. Across diverse measures and regions, women consistently exhibited higher EE scores (Cohen’s d = 0.39). Young adults and students showed a stronger association with EE, suggesting heightened vulnerability. Key predictors included increased food intake, COVID-19-related stress and lifestyle changes, sleep quality, and physical activity.ConclusionThe predominance of cross-sectional designs limits the ability to draw causal conclusions, and selection bias in studies, often targeting specific groups, restricts generalizability. Future longitudinal studies are needed to assess causality and explore the inferences to additional factors, such as socioeconomic status and mental health. Gender-sensitive interventions are suggested to address EE risks, particularly in women.Systematic review registrationPROSPERO (CRD42023421727). https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42023421727.